EFFECT OF PUDDLING PRACTICES AND CROP ESTABLISHMENT METHODS ON THE PRODUCTIVITY OF RICE (ORYZA SATIVA.L) (The Journal of Research ANGRAU, 2026)
A  research  trial was conducted in clay loam soils at  Regional Agricultural Research Station,Maruteru, Andhra Pradesh during rabi, 2022-23 to assess the effects of puddling and cropestablishment methods on rice productivity.The study comprised two factors:  puddling practice,viz., power tiller (M1), rotovator (M2,) and roto-puddler (M3) as main plot treatments and cropestablishment method, viz..,drum seeding (E1),line planting (E2),machine planting (E3),diagonalplanting (E4,) and Bengal planting (E5) as sub-plot  treatments.The results showed that amongthe puddling practices, the use of a roto-puddler registered the highest growth parameters atharvest, such as number of tillers m-2 (401), crop dry matter (11053 kg ha-1), and yield attributes,that is, the number of panicles m-2 (371), total number of grains panicle-1 (259), grain (4697 kgha-1), and straw yield (6098 kg ha-1). This was statistically at par with the use of a rotovator butsignificantly superior to that of a power tiller. Among crop establishment methods, growthparameters at harvest, that  is, number of tillers m-2 (416), crop dry matter (11427 kg ha-1), andyield parameters, that is, the number of panicles m-2 (386), total number of grains panicle-1 (257),grain (4837 kg ha-1), and straw  yield (6148 kg ha-1) were higher with the diagonal planting method;however, it was  found statistically at par with Bengal planting and drum seeding but significantlysuperior over machine planting  and line planting.